2017
DOI: 10.1590/s1980-6574201700si0087
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural study of physical activity and sedentariness in youth from Mozambique and Portugal

Abstract: -Aim:The purpose of this study was to analyse the effects of age, sex, body mass index (BMI) and country of origin (Mozambique versus Portugal) on physical activity and sedentariness. Methods: Sample size was comprised of 593 adolescents from Mozambique (n=258) and Portugal (n=335), aged 10-15 years old. Height and weight were measured, and BMI was computed; furthermore, subjects were classified in two groups (normal weight and overweight/obese). The mean time (min/day) spent in moderate-to-vigorous physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This result is consistent with Alemdağ's (2017) research. Santos et al (2017) surveyed Mozambican and Portuguese young people and found that Mozambicans are less involved in physical activity than the Portuguese. They associated this result with the undesirable effect of urbanization in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with Alemdağ's (2017) research. Santos et al (2017) surveyed Mozambican and Portuguese young people and found that Mozambicans are less involved in physical activity than the Portuguese. They associated this result with the undesirable effect of urbanization in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary to Africa, few studies have used objective methods to assess PA among children and estimates of physical activity or sedentary behavior has derived mostly from self-report questionnaires. Indeed, a review of Peltzer reported that only 14.2% of children from 8 countries were physically active (5 days or more in a week with at least 60 min/day) and there are large differences among countries meeting the PA guidelines, 17.7% in Uganda and 9.0% in Zambia through self-report questionnaires [ 6 ], 3.9% in Mozambique [ 7 ], 1% in South Africa using GT3X accelerometer [ 8 ], and 54.8% in Senegal using GT3X+ accelerometer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%